Sex Dolls in Islamic Thought: A Qur’anic and Maqasidic Analysis of Sexuality and Tamatsil - Wicaksono, Muhammad Pradipa; Hakim, Lukmanul; Saifullah, Saifullah; Nixson, Nixson; Putra, Masyhuri (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
The increasing use of sex dolls raises ethical, social, and religious concerns, particularly in Islamic discourse. While Islamic scholarship has extensively discussed sexuality and statues (tamatsil), there remains a research gap in analyzing their intersection within modern technology. This study examines the permissibility of sex dolls within Islamic ethics and law by integrating Qur’anic interpretation and Maqasid al-Shariah. A qualitative hermeneutical and thematic (tafsir maudhu’i) approach is employed to analyze Surah Al-Ma'arij (70:29-31), Surah Saba’ (34:13), and Surah Al-Anbiya' (21:52). Classical and contemporary exegeses, along with fatwas from Dar al-Ifta' Egypt, Saudi Arabia, and Indonesia, provide legal insights. Findings indicate that sex dolls contradict Islamic ethical principles, particularly hifz al-‘ird (preserving dignity), hifz an-nasl (preserving lineage), and hifz al-aql (preserving intellect). Fatwas classify sex dolls as haram due to their potential to normalize unethical behavior and disrupt marital relationships.